Is Field of Study or Location Associated with College Students' Snacking Patterns? - Laura H. McArthur; Donald Holbert; William Forsythe (Journal of Obesity)
Objective. To compare on- and off-campus snacking patterns among college students pursuing degrees in health-related fields (HRFs) and nonhealth-related fields (NHRFs). Materials and Methods. Snack frequency questionnaire, scales measuring barriers, self-efficacy, and stage of change for healthy snacking, and a snack knowledge test (SKT). Participants. 513 students, 46% HRFs, and 54% NHRFs. The students' mean±SD BMI was 24.1±4.3 kg/m2 (range 14.6 to 43.8), and 32.2% were overweight/obese. Results. Softdrinks (on-campus), lowfat milk (off-campus), and sports drinks were popular among HRFs and NHRFs. Cost and availability were barriers to healthy snacking, students felt least confident to choose healthy snacks when emotionally upset, and 75% (65%) of HRFs (NHRFs) self-classified in the action stage of change for healthy snacking. The HRFs scored higher on the SKT. Conclusions. Neither location nor field of study strongly influenced snacking patterns, which featured few high-fiber foods.